Corruption, economic growth and sustainable development - a conditional quantile analysis. (5th May 2022) - Castro, Conceição; Pinho, Carlos
Corruption strangles not only economic growth and but also sustainable development, which comprises the economic, social, and environmental dimensions of development. This paper aims to analyse the effects of corruption on economic growth and sustainable development, measured by the adjusted net savings. Using a quantile regression approach, this paper develops a panel data model allowing the analysis of different potential effects in the relationships corruption - economic growth and corruption - sustainable development. This is done along different points of the conditional growth and sustainable development distributions in a sample of 134 countries during the period 2000-2018. The results suggest that corruption decreases GDP per capita and sustainable development despite its levels. But the magnitude of the effects of corruption increases as one moves from the higher to the lower tail of the conditional distribution of GDP per capita or sustainable development. Consequently, lower-performing countries could benefit more from reducing corruption. Controlling corruption can thus be seen as an effective way to promote growth and sustainable development.